The identity of two obscure names of Violaceae from the Flora Brasiliensis context: nomenclatural novelties within Hybanthus communis - Paula-Souza, Juliana de; Moraes, Pedro L. R. de [UNESP] (Soc Royal Botan Belgique, 2015)
Background and aims - Ionidium racemosum Nees &Mart. and I. maximilianii Eichler had their identities obscured by missing types and poor descriptions. Recent searches through historical collections revealed that they are synonyms of Hybanthus communis (A.St.-Hil.) Taub., and the nomenclatural revision that followed this finding required some typological adjustments that are presented here.Methods - The main collections known to house specimens from the context of Flora Brasiliensis were consulted, especially in Europe and North America. Further searches were performed at the libraries and archives of these institutions or on the intemet, in order to gather pertinent historical literature.Key results - A nomenclatural revision of Hybanthus communis is provided with a historical background to support the typological modifications that were performed. Three lectotypifications and four new synonyms are presented here.
Keywords: Historical collections; Flora brasiliensis; Hybanthus communis; Lonidium maximilianii; Lonidium racemosum; Nomenclature; Taxonomy; Violaceae